Collaborative Governance: Managing Residential Areas In Malang Based on Public Private Partnership - Fitri Amalia Sari; Sudarmo Sudarmo; Didik G. Suharto; Nida Hanin Dary (Indonesian Association for Public Administration (IAPA), 2019)
Slum areas are one of in Malang problems as the second largest city in East Java, especially along the Brantas River in the area of Jodipan village. According to Malang Local Government, Brantas River area is an area designated as a Green Space. Rearrangement of this area has not been done by the Local Government, and the area has turned into a densely populated area and Tourism Village. Guys Pro student group cooperates with PT. Indana Paint and supported by Malang Mural community are trying to promote the area. Although this violates existing regulations, the government still legalizes colorful villages as tourism areas. This is because the government has not been able to provide enough space to relocate citizen. Collaboration needs to be done by the Government with private sector to relocate citizen and rearrange tourism areas on the banks of Brantas River. PPP scheme will help government in handling costs and resources by the private sector. This research was conducted with descriptive qualitative and literature review methods. This research seeks to examine the innovations that the government can do in improving the governance of that area through citizen relocation and structuring of the Brantas river bank through PPP collaboration.